The newest diversity is the oldest: Religious pluralism and the EU. (August 2014) - Zanon, Flavia; Sciortino, Giuseppe
Since the 1990s, the expansion of the European Union's competences to new policy fields and the entrance of new member states with recent histories of religious repression have increased the exposure of European Union institutions to issues having a potentially high impact on religious sensitivity. Because the differentiation between the religious and the political in Europe has never been complete, national laws and regulations have always reflected different forms of compromise between states and majoritarian religious churches. The involvement of supranational institutions could be a challenge to this variety of situations. The approach developed by EU institutions to deal with issues of religious diversity, however, severely minimizes the chances of any active intervention in country-level compromises, thereby leaving the resolution of contemporary challenges concerning religion in Europe to the national level. This situation points at the persistent absence of shared principles and values concerning a core component of a common European identity.